Unraveling the Epistemology of Islamic Economics: Insights from Abdul Hamid Ahmed Abu Sulayman's Thought - Ismail, Nurizal; Siti Aisyah (El-Barka, 2024)
Epistemology of Islamic economics from the thought of Abu Hamid Sulayman is important to be studied as one of the Muslim prominent thinkers in the Islamization of Knowledge (Iok). Research Methods: The study adopts a qualitative methodology, employing thematic analysis to explore Abdul Hamid Ahmed Abu Sulayman's economic ideas as presented in his works on the epistemology of Islamic economics. Results: The study indicated that AbuSulayman's thought of Islamic economics revolves around an epistemological structure based on Islamization of knowledge framework. Conclusion: AbuSulayman's proposal for Islamic economics adopts an epistemological approach rooted in the Islamic worldview, utilizing the Islamization of knowledge framework, specifically asalah wal mu'asirah.